Listening to Art Song: An Introduction - Olson, Margaret (Rowman & Littlefield Publishers, 2015)
Listening to Art Song: An Introduction offers an easy-to-read, fresh perspective on the remarkably diverse musical genre of art song. As the ultimate expression of the human singing voice, song has provided succor and entertainment to humanity in many forms since the dawn of civilization. Margaret Olson examines art song’s development, outlines the elements that comprise it, offers ideas on how to effectively listen to it, provides brief biographical sketches of key art song composers, and lists important recordings in the Italian, French, German, British, and American art song traditions. By instructing readers in how to evaluate art songs, Olson informs and enhances the art song experience for listeners. Listening to Art Song is the ideal text for any student studying voice or anyone interested in the genre of song.